New York Convention convention on the recognition and enforcement of foreign arbitral awards of 10 June 1958 ; commentary - Wolff, Reinmar; Borris, Christian 1956-. (M?unchen, Germany Oxford, United Kingdom Baden-Baden, Germany C.H. Beck Hart Nomos, 2012)
In a world characterised on the one hand by globalised trade and commerce, and on the other by deteriorating judicial services, arbitration has become the dispute resolution mechanism of choice in cross-border commercial transactions. International arbitration not only paves the way for parties to avoid state courts, it also facilitates the transnational enforceability of awards that are far more effective than the enforceability of state court judgments. The major instrument is the Convention on the Recognition and Enforcement of Foreign Arbitral Awards (New York Convention) of 10 June 1958, which entered into force one year after. Since then the New York Convention has been ratified by 144 states, including all the important trading nations. For good reason the New York Convention is labelled the Magna Carta of international arbitration. The courts of any contracting state are required 'to give effect to an agreement to arbitrate when seized of an action in a matter covered by an arbitration agreement and also to recognize and enforce awards made in other States, subject to specific limited exceptions' (UNCITRAL). The 16 articles of the Convention are dealt with article-by-article, following a clear structure which swiftly guides the reader to the issue that he or she is engaged with. Given the New York Convention's global relevance, it follows that potential users of the Convention are in need of guidance as to how to apply it. The primary readers of this book will be lawyers seeking (or defending against) recognition and enforcement of foreign arbitral awards worldwide, state court judges applying the Convention in recognition proceedings, and in-house lawyers in large and/or multinational enterprises dealing with transnational dispute resolution.
Includes bibliographical references and index.
Keywords: Convention on the Recognition and Enforcement of Foreign Arbitral Awards -- (1958).; International commercial arbitration; Arbitration agreements, Commercial